2010
DOI: 10.1007/s10705-009-9341-0
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between nitrogen, phosphorus and potassium determine growth and N2-fixation in white clover and ryegrass leys

Abstract: Variations in yield, N 2 fixation and above-ground accumulation of nitrogen (N), phosphorus (P) and potassium (K) in white clover and ryegrass grown separately or in mixture were investigated under field conditions over two consecutive years at different supplies of N, P and/or K. Ryegrassclover mixtures consistently out-yielded the pure stand clover and pure stand ryegrass in terms of dry matter. Improved N supply favoured ryegrass, and ryegrass in mixture with clover accumulated substantially higher amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…The variation in soil fertility is often related to below-ground species richness that may influence the function of ecosystems via nutrient supply (Naeem et al, 1995;Ekschmitt & Griffiths, 1998) which in turn influences the botanical composition (Høgh-Jensen & Schjoerring, 2010;Rasmussen et al, 2007). Increasing the supply of N to temporary grassland was shown by Mudd (1970) to decrease herbage Mn, which is confirmed in this study (data not shown).…”
Section: G Kgsupporting
confidence: 83%
See 2 more Smart Citations
“…The variation in soil fertility is often related to below-ground species richness that may influence the function of ecosystems via nutrient supply (Naeem et al, 1995;Ekschmitt & Griffiths, 1998) which in turn influences the botanical composition (Høgh-Jensen & Schjoerring, 2010;Rasmussen et al, 2007). Increasing the supply of N to temporary grassland was shown by Mudd (1970) to decrease herbage Mn, which is confirmed in this study (data not shown).…”
Section: G Kgsupporting
confidence: 83%
“…One of them may lie in the release of these nutrient elements from the various species and organs, not to mention cell fractions (Whitehead et al, 1985;Ibrahim et al, 1990). Another may lie in nutrient interactions, for example N, P and K interaction, which Høgh-Jensen and Schjoerring (2010) demonstrated to determine the competitive ability in a two-species mixture. A third may be that some systems favour productivity and resource-use efficiency, which may give lucerne, red clover and festulolium an advantage, 88 H. Høgh-Jensen & K. Søegaard while others may favour persistence to grazing which may give ryegrass and white clover some advantages.…”
Section: G Kgmentioning
confidence: 99%
See 1 more Smart Citation
“…No increase of the P concentration was observed after application of slurry or slurry fractions. Similar P concentration values in ryegrass were observed by Høgh‐Jensen and Schjoerring (2010), while Starnes et al (2008) reported values considerably higher.…”
Section: Discussionsupporting
confidence: 84%
“…The N concentration values in dry biomass, observed in the first cut, were in the range of values reported in other studies ( Høgh‐Jensen and Schjoerring , 2010; Grigatti et al, 2011) and can be considered as adequate according to the classification from Reuter and Robinson (1997). However, N concentrations in the materials harvested at the second cut were all very low and indicated N deficiency.…”
Section: Discussionsupporting
confidence: 76%